C9orf72 Alleviates DSS‑Induced Ulcerative Colitis via the cGAS‐STING Pathway - Yue Wang; Ting Xu; Wenjun Wang (Immunity, Inflammation and Disease)
ABSTRACT Purpose C9orf72 deficiency contributes to severe inflammation in mice. Ulcerative colitis (UC) is a chronic inflammatory disorder with the shortage of clinical success. However, whether C9orf72 is involved in the progression of UC is not fully understood. This study investigated whether C9orf72 could alleviate dextran sulfate sodium (DSS)‐induced colitis in mice and lipopolysaccharide (LPS)‐induced colitis in Caco‐2 cells. Methods Mice were injected AAV9‐C9orf72 lentivirus through tail vein and fed 3% DSS for a week. Caco‐2 cells were cultured to establish C9orf723 overexpressed model. Histopathological examination, level of inflammation, cGAS‐STING pathway, and gut barrier function were detected in mice and cells. Results C9orf72 overexpression in mice attenuated DSS‐induced colitis and intestinal epithelial barrier damage by stimulating ZO‐1 and Occludin expression. In LPS‐induced Caco‐2 cells, C9orf72 overexpression increased cell viability and the expression of ZO‐1 and Occludin. C9orf72 overexpression alleviated inflammation by inhibiting the cGAS‐STING pathway in colonic tissue and Caco‐2 cells. Conclusion C9orf72 overexpression attenuated DSS‐induced colitis and intestinal epithelial barrier damage by inhibiting the cGAS‐STING pathway. C9orf72 may present a target for mitigating UC.